Effects of enamel and dentine thickness on laser doppler blood-flow signals recorded from the underlying pulp cavity in human teeth in vitro - P. Banthitkhunanon (2018)
Objective: To determine the effect of enamel and dentine thickness on laser Doppler blood-flow (LDF) signals recorded from dental pulp. Design: Observations were made on 18 human premolars that had been extracted from young patients during orthodontic treatment. The apical 2/3 of the root was cut off and the remaining pulp removed. Blood flow signals were recorded from the buccal surface of the crown with a laser Doppler flow metre while dilute blood was pumped at 10 ml/min. through a cannula inserted into the pulp cavity. Recordings were made from the enamel surface and at 0.5 mm steps through the enamel and dentine. Results: The blood flow signal increased significantly as the cavity depth increased and at 2.0 mm, the median flux signal was more than ten times greater than that obtained on the enamel surface. The backscattered light intensity did not change with cavity depth. Conclusion: When recording pulpal blood flow from a human tooth with a laser Doppler flow metre, a substantially better signal-to-noise ratio should be obtained by placing the probe on dentine in the floor of a cavity than on the enamel surface. © 2013 Elsevier LtdElsevier Ltd. All rights reserved.